PROPOSAL FOR THE IMPLEMENTATION OF SPRAY DRYING IN THE ACTIVATION PROCESS OF BENTONITE WITH SULFURIC ACID - Romero, P. (2010)
The present work propose the replacement of the three stages of the activation process of bentonite with sulfuric acid by the only stage spray drying.